Inferior : how science got women wrong and the new research that's rewriting the story - Saini, Angela, 1980- (Beacon Press, 2017)
"What science has gotten so shamefully wrong about women, and the fight, by both female and male scientists, to rewrite what we thought we knew. For hundreds of years it was common sense: women were the inferior sex. Their bodies were weaker, their minds feebler, their role subservient. No less a scientist than Charles Darwin asserted that women were at a lower stage of evolution, and for decades, scientists--primarily men--claimed to find evidence to support this. From intelligence to emotion, cognition to behavior, science has continued to tell us that men and women are fundamentally different. Biologists claim that women are better suited to raising families or, more gently, uniquely empathetic. Men, on the other hand, continue to be described as excelling at tasks that require logic, spatial reasoning, and motor skills. But a huge wave of research is now revealing an alternative version of what we thought we knew. The new woman revealed by this scientific data is as strong, powerful, strategic, and smart as anyone else. In Inferior, acclaimed science writer Angela Saini weaves together a fascinating--and sorely necessary--new science of women. She takes readers on a journey to uncover science's failure to understand women and to show how women's bodies and minds are finally being rediscovered. Saini tells this alternate story of science with personal stories, controversial research, and an investigation into the gender wars in biology, psychology, and anthropology"--